Respon Pertumbuhan Bibit Picrasma javanica Blume terhadap Intensitas Naungan dan Media Tanam - Ninik Setyowati; Ning Wikan Utami (Universitas Atma Jaya Yogyakarta, 2009)
Study on the growth response of Picrasma javanica Blume seedling to different shading intensities and medium was conducted at the Experimental Garden of Treub Laboratory, Research Centre for Biology, LIPI from June to December 2007. The research was arranged using Factorial in Completely Randomized Block Design with 2 factors and 5 replications. The first factor was shading intensities which were 0% (N0, without shading, average light intensities 39300 lux), 25% (N1, average light intensities 16430 lux), and 50% (N2, average light intensities 5867 lux), respectively and the second factor was medium (combinations of soil: manure:compost) with 6 levels were M1= 1:0:0, M2= 1:1:1, M3= 1:1:2, M4= 3:1:1, M5= 1:2:1, and M6= 2:1:1. The result showed that the N0 treatment (without shading) resulted the best growth response of Picrasma javanica Blume seedling, as showe in all parameters observed (plant height 27.11 cm; leaf number 15.57; diameter of trunk 4.32 mm; and root length of 15.97 cm, shoot dry weight of 1.762 g, root dry weight of 0.688 g and seedling quality index of 0.277). The growth media treatment of M5 (1-soil:2 manure:1 compost) showed the positive response on the growth of seedling better than other treatments and different with control (M1, soil media), with parameters were observed which was plant height 25.05 cm (M1= 19.10 cm); leaf number 16.53 (M1= 9.20); diameter of trunk 3.89 mm (M1= 2.76 mm); root lengh 15.23 cm (M1= 12.71 cm); shoot dry weight 1.58 g (M1= 0.663 g); root dry weight 0.51 g (M1= 0.221 g) and seedling quality index 0.220 (M1= 0.089). The combination treatment of N0 (without shading) and media M5 (1:2:1) gave the best response on the growth of Picrasma seedling (plant height 36.14 cm; leaf number 28.2; diameter of trunk 4.7 mm; and root length 16.7 cm, shoot dry weight 3 g and root dry weight 0.92 g).